Penggunaan Kamus Olahraga Berbasis Android dalam Penguasaan Istilah Asing Bidang Olahraga: Use of Android-Based Sports Dictionary in Mastering Foreign Terms in the Field of Sports - Setyawan, Farid Helmi; Bajuri, Puput Eka (Universitas Muhammadiyah Sidoarjo, 2018)
Based on the observation in the field, there are many problems with the meaning of the foreign word. From 100 students, 25 collage students and 25 teachers that become respondent, the average of them had the same problem about the meaning of the word or foreign vocabulary. This research aimed to describe the effectiveness of using sports dictionary based android system in teaching foreign vocabulary in sport areas. The method used in this research is Research and Development (R & D). The developed media is a sports dictionary with an Android system. The results showed that out of 150 respondents, 93% or 140 people agreed with the application. The application is very helpful for them in finding the meaning of a foreign term in the field of sports. From 150 respondents, 86 said the application was good in the system and appearance, 53 people said the application made searching easier but the display was still lacking, and 11 people said the application was normal and not helpful. The test results of using the application show 85% of respondents are easier to understand and remember the existing vocabulary. The findings of this study are the use of sports dictionary applications based android and combined with appropriate learning methods obtained the results of mastering foreign words in the field of sports can be maximised.